2005
DOI: 10.1128/jvi.79.5.2709-2719.2005
|View full text |Cite
|
Sign up to set email alerts
|

Early Antiretroviral Therapy for Simian Immunodeficiency Virus Infection Leads to Mucosal CD4+T-Cell Restoration and Enhanced Gene Expression Regulating Mucosal Repair and Regeneration

Abstract: Simian immunodeficiency virus (SIV) and human immunodeficiency virus (HIV) infections lead to rapid depletion of CD4؉ T cells from gut-associated lymphoid tissue (GALT). Although the administration of antiretroviral therapy (ART) has been shown to increase CD4 ؉ T-cell levels in the peripheral blood in both SIV and HIV infections, its efficacy in restoring intestinal mucosal CD4؉ T cells has not been well investigated. To gain insights into the molecular mechanisms of virally induced disruptions in the mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
118
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 45 publications
(58 reference statements)
9
118
0
Order By: Relevance
“…So there maybe exist difference in leukocyte subpopulations counts of these two animals. The baseline levels of CD4 + T cells of Indian rhesus macaques were 1369 cells/μl (median number) in Reimann et al's study (33) and 1300 cells/μl in George et al's study (34). Chinese rhesus macaques analyzed in Qiu et al's (1661 ± 777 cells/μl) and our study (1611 ± 718 cells/μl) showed a higher CD4 + T cells counts.…”
Section: Discussionsupporting
confidence: 42%
“…So there maybe exist difference in leukocyte subpopulations counts of these two animals. The baseline levels of CD4 + T cells of Indian rhesus macaques were 1369 cells/μl (median number) in Reimann et al's study (33) and 1300 cells/μl in George et al's study (34). Chinese rhesus macaques analyzed in Qiu et al's (1661 ± 777 cells/μl) and our study (1611 ± 718 cells/μl) showed a higher CD4 + T cells counts.…”
Section: Discussionsupporting
confidence: 42%
“…Hence HIV infection could quite reasonably be considered a disease of the GI tract. Our new understandings in this regard have pointed to new therapeutic directions: the aim would be to prevent or reduce the propagation of HIV at mucosal surfaces 35,102 and to restore the immunological and epithelial integrity of the mucosal barrier. 35 …”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, SIV-infected macaques also manifest enteropathy, 34 which is associated with decreased expression of genes such as trefoils that are involved in mucosal repair. 35 Hence, in pathogenic SIV infection of rhesus macaques, the majority of the body's CD4 T cells are depleted within the short acute phase of the infection -a finding not reflected by analysis of peripheral blood or lymph nodes.…”
Section: Gastrointestinal Cd4 T-cell Depletionmentioning
confidence: 99%
“…4B) in intestinal mucosa that are required for normal maturation of enterocytes. In the SIV model, multiple growth factors as well as genes mediating intestinal epithelial (enterocyte) repair and regeneration have been shown to be dysregulated in GALT during primary acute and chronic stages of infection (6)(7)(8)(9)(10). Moreover, SIV-infected macaque studies have demonstrated impaired nutrient digestive and adsorptive functions during primary SIV infection (6).…”
Section: Discussionmentioning
confidence: 99%